(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to examine the level and relationship between supply chain management practices (SCMP), and supply chain innovation (SCI) among SMEs in Malaysia. Manufacturing supply chain needs to innovate constantly for maintaining their position in the marketplace and also to fight uncertainties. Hence firms are focusing on strategies for developing innovation within and across its manufacturing supply chain. In line with following objectives, this study employs a quantitative research approach which will utilities stratified sampling technique and self-administered questionnaire survey. The respondents for this survey will be the individuals in operations of SMEs business in Malaysia. Subsequently, the survey data will be utilized to test the research framework and hypotheses. The results of the study can be useful for supply chain practitioners and manufacturers in integrating the right SCMPs on improving SCI. Furthermore, industrial practitioners will also receive insight on how to take account of the effect of SCMPs in designing their supply chain innovation for better manufacturing performance. In fact, organizations are not certain of what to implement, due to a lack of understanding of what constitute a comprehensive set of SCMPs. Also, the result will suggest successful dimensions of SCMPs that is could be implemented in order to foster supply chain innovation in SMEs in Malaysia.